Sessões de biofeedback ambulatorial adicionadas ao treinamento domiciliar dos músculos do assoalho pélvico para tratamento da incontinência urinária de esforço - ensaio clínico randomizado controlado - Fitz, Fatima Fani [UNIFESP] (2017)
Aims: To test if biofeedback (BF) added to pelvic floor muscle training (PFMT) increases the frequency of home exercises performed by women with stress urinary incontinence (SUI). Methods: 72 incontinent women were randomized to BF (outpatient BF + home PFMT) or PFMT (outpatient PFMT + home PFMT) groups. Assessments: baseline, after 3 months of supervised treatment, at 9month follow-up (after 6 additional months of home PFMT only). Primary outcome: frequency of monthly exercises sets performed (exercise diary) and cure of SUI (pad test <2g leakage) after 3-month treatment. Secondary outcomes: urinary symptoms, severity and cure of SUI (pad test <2g leakage), muscle function, adherence, quality of life, and subject cure (satisfaction report with no desire for different treatment) at the two time-points. Statistical analyses: ANOVA and Student’s t-test with 5% cut-off for significance. Results: It was observed similar frequency of monthly home exercises sets performed by BF (67.9 out of 82) and PFMT (68.2 out of 82) groups at three months. Secondarily, equal satisfaction, but superior objective cure of SUI for BF group after 3-month treatment [p=0.018; OR: 3.15 (95% CI: 1.20 – 8.25)]. At 9-month follow-up, the adherence to home exercises was similar (around 50%) and significantly dropped in both groups compared to the 3-month results (around 85%). No difference was detected in the objective and subjective cure of SUI between the groups after 9 months. Both therapies similarly improved the muscle function and quality of life during the study (p<0.005). Conclusions: Adjunct BF did not increase the frequency of home exercises performed by SUI patients, however, an increase in the objective cure rate of SUI was observed.